The relationship between the awareness of green office practices and employee's job satisfaction in SAJ Holdings Sdn Bhd Agency Yong Peng / Alia Atiqah Abd. Razak - Abd. Razak, Alia Atiqah (2014)
Green Office is an environmental management system for offices. With its help, workplaces are able to reduce their burden on the environment, achieve savings and slow down climate change. Nowadays, companies have another reason to go green. New research has found that companies that adopt eco-friendly green practices have employees that are more productive than those that do not. The objective of this research was to identify the awareness on green office practices among employees in SAJ Holdings Sdn. Bhd. Agency Yong Peng. This research also conducted to examine the relationship between green office practices and employee's job satisfaction among employees in SAJ Holdings Sdn. Bhd. Agency Yong Peng. A questionnaire was used as the main instrument and the data was analysed using SPSS version 21.0. The questionnaire was distributed personally to the respondents in SAJ Holdings Sdn. Bhd. Agency Yong Peng. Besides that, the respondents were assisted by the researcher and research assistant in choosing the degree of agreement on each of the statement. It was found that the employees in SAJ Holdings Sdn. Bhd. Agency Yong Peng has a high level of awareness of green office practices towards 3R practices and energy use in their organization. From the findings, it shows that majority respondent has awareness towards 3R practices (recycle, reuse, reduce) in the organization is average with (M=3.96, SD=0.694). While the level awareness of green office practices towards energy use is (M=4.248, STD=0.524). In addition, from the result it indicated there is a strong relationship between the awareness of green office practices and employee' s job satisfaction in SAJ Holdings Sdn. Bhd. Agency Yong Peng. The Pearson Correlation (r) for mean level of awareness towards 3R practices and employee job satisfaction is (r= .624** , n=76, p<.05, s=.001). Then, for mean level of awareness towards energy use and employees job satisfaction is(r= . 750* *, n=76, p<.05, s=.001). So, it indicated that Hypothesis !(There is a relationship between the level of awareness towards 3R practices and employee job satisfaction in SAJ Holdings Sdn. Bhd Agency Yong Peng) and Hypothesis 2 (There is a relationship between the level of awareness toward energy usage and employee job satisfaction in SAJ Holdings Sdn. Bhd Agency Yong Peng.) is accepted in this research.